Palm Oil Land Litigations in Indonesia: Cases Involving Malaysian MNE Sime Darby Plantation Berhad - Dahlan, Nuarrual Hilal Md; Yusuff, Yusramizza Md Isa; Khalid, Al-Hanisham Mohd (ExcelingTech, 2019)
Malaysia currently accounts for 39% of world palm oil production and 44% of world exports. Being one of the biggest producers of palm oil, Malaysia has an important role to play in fulfilling the global demand for palm oil. With the growing global demand for palm oil, Malaysian Multinational Enterprises (MNEs) have embarked on the expansion of palm oil plantations by venturing into cross border palm oil plantation ventures including Indonesia. Nonetheless, the cross border venture may not an easy project, as the MNEs have encountered unprecedented challenges. Currently, land conflict in palm oil plantation ventures in Indonesia is one of the main impediments for Malaysian MNEs implementing investment in Indonesia. This issue if not resolved can lead to the failure of the MNEs’ investment and may affect FDI flows into Indonesia. The main objective of this paper is to examine the case law litigation and related information elicited from qualitative sources and interviews with relevant persons involving land issues in carrying out palm oil plantation ventures in Indonesia by Sime Darby Plantation Berhad (‘SDPB’)(being a subsidiary of Sime Darby Berhad). Qualitative social and legal research methodologies were used in this writing. From this writing, certain information can be generated to illustrate the problems and their causes arising from land conflict in palm oil plantation ventures in Indonesia and the approaches that have been undertaken by the investors to deal with the problems. The findings of the writing will add knowledge to relevant persons in understanding the dynamic challenges that are faced by Malaysian MNEs in its internationalization of palm oil plantation ventures.